2021
DOI: 10.1155/2021/6692410
|View full text |Cite
|
Sign up to set email alerts
|

Business Owners’ Feedback toward Adoption of Open Data: A Case Study in Kuwait

Abstract: The world intention toward open data technology has increased in the past years, and governments started to explore open data technology in the public and private sectors and tried to check its advantages and disadvantages. However, in the Arab world and especially in Kuwait, there is no solid structured attention about the technology in both sectors. As a result, we tried in this paper to determine if business owners in Kuwait have enough knowledge of the open data (OD) concept and if they have the willingnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…In KIBS [Santos, Spring, 2015], there is a need to improve the knowledge of SMEs in other areas, such as e-business [Archer et al, 2008] or Open Data [Alawadhi et al, 2021]. CE affects sales in a significant way (83% compared to advertising (15%)) [Li et al, 2011].…”
Section: Implementation Of Ce Across Industriesmentioning
confidence: 99%
“…In KIBS [Santos, Spring, 2015], there is a need to improve the knowledge of SMEs in other areas, such as e-business [Archer et al, 2008] or Open Data [Alawadhi et al, 2021]. CE affects sales in a significant way (83% compared to advertising (15%)) [Li et al, 2011].…”
Section: Implementation Of Ce Across Industriesmentioning
confidence: 99%
“…In this stage, nine more articles were excluded as not fitting one or more of the inclusion criteria, and one paper (Syaifuddin et al, 2022) was excluded as the original UMEGA was distorted to a large extent by making the mediator attitude an independent variable, resulting in a total of 10 eligible papers, aligned with the objectives of the study. Finally, as structural model analysis or path co-efficient was not reported, one more paper (Alawadhi et al, 2021) was excluded, thus yielding nine papers (Table 1) being reviewed finally and analyzed in this systematic literature review.…”
Section: Article Eligibilitymentioning
confidence: 99%
“…Their research presents the ENGAGE open data infrastructure, the aim of which is to serve as a pipeline for publishing OGD in accordance with novel Web 2.0 oriented functionalities. Alawadhi et al (2021) found that the existence of adequate strategies for publishing OGD would contribute to valuable deliverables. Consequently, this boosts income and productivity, affecting positively the economic cycle in the countries and encouraging the government sector to support the concept of open data and enact the necessary laws for that.…”
Section: Quality Of Open Government Datamentioning
confidence: 99%